LEGAL PROTECTION FOR OWNERSHIP OF PROPERTY LAW ON MARRIAGE AFTER DIVORCE DECISION - Sugiarti Sugiarti (President University, 2015)
Marriage is a sacred and holy institution as stated in Law No. 1 of 1974 article 1 about marriage. Joint property can be used by the husband and wife, for anything and any amount as long as there is also agreement of both parties. Just right for a husband and wife with the right of use or wear it with the consent of both parties (reciprocal) is naturally given that the rights and position of the wife by the husband is in an environment of domestic life and social life together in society, a place where each each has the right to take legal actions. This means that both parties are given the opportunity to have an agreement that's about innate property may be inserted into the joint property, while other parts are certain to remain under the supervision of each. If each party has an agreement to enter the default property to be joint property, the management is certainly applicable provisions of the agreement regarding the default property.